2019
DOI: 10.12659/ajcr.916368
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hyperkalemia Immediately After Birth

Abstract: Patient: Male, newbornFinal Diagnosis: HyperkalemiaSymptoms: Respiratory distress • ventricular tachycardiaMedication: —Clinical Procedure: Exchange transfusionSpecialty: Pediatrics and NeonatologyObjective:Unknown ethiologyBackground:Hyperkalemia is an important cause of arrhythmias and a medical emergency that requires urgent treatment. The etiology is usually multifactorial. It is most frequently caused by impaired potassium secretion, followed by transcellular potassium shifts and an increased potassium lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A number of clinical case reports have documented TAHCA in patients receiving large volume transfusions, although we have also highlighted reports of TAHCA following rapid, small volume transfusions of older and/or irradiated blood products (66,67,82,84,88,89,91). Inoue et al, observed peaked T-waves immediately after administering 10 mL of blood via handheld syringe to a 1.4kg newborn (82).…”
Section: Tahca In Neonatal Infant and Pediatric Patientsmentioning
confidence: 69%
See 1 more Smart Citation
“…A number of clinical case reports have documented TAHCA in patients receiving large volume transfusions, although we have also highlighted reports of TAHCA following rapid, small volume transfusions of older and/or irradiated blood products (66,67,82,84,88,89,91). Inoue et al, observed peaked T-waves immediately after administering 10 mL of blood via handheld syringe to a 1.4kg newborn (82).…”
Section: Tahca In Neonatal Infant and Pediatric Patientsmentioning
confidence: 69%
“…Nevertheless, hyperkalemia from blood transfusion is the second most common cause of perioperative cardiac arrest in neonates, infants, and children as documented by the perioperative cardiac arrest registry, second only to hypovolemia from blood loss (74). In Table 1, we have summarized 24 case studies and reports of TAHCA in neonatal, infant, and pediatric patients -with data reported as indicated in the original article (25,37,39,40,66,67,71,(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). We also highlight a case report in which TAHCA was avoided by pre-transfusion K + filtration (87).…”
Section: Tahca In Neonatal Infant and Pediatric Patientsmentioning
confidence: 99%